A measurement method for the overturning coefficient of high-speed trains passing through complex terrain sections under strong wind conditions. (September 2020) - Lu, Zhaijun; Huang, Weijia; Zhong, Mu; Liu, Dongrun; Li, Tian; Zhan, Huan
Real-time monitoring of overturning coefficients is very important for ensuring the safety of high-speed trains passing through complex terrain sections under strong wind conditions. In recent years, the phenomenon of "car swaying" that occurs when trains pass through the complex terrain has brought new challenges to ensuring the safety and riding comfort of passengers. In China, more and more high-speed trains are facing strong wind environments when running in complex terrain sections. However, due to the limitation of objective conditions, so far, only a few economical and effective methods of measurement have been developed that are suitable for real-time monitoring of the overturning coefficient of commercial vehicles. Therefore, considering the applicability and universality of such a monitoring method, this study presents a method for measuring the overturning coefficient of trains using the primary suspension system under strong winds. A vehicle test was carried out to verify the accuracy of the method. The results show that after correction, the overturning coefficient obtained from the primary suspension system is generally consistent with the overturning coefficient obtained from the instrumented wheelset. The method of measuring the overturning coefficient of trains in strong wind environments with the primary suspension system is, thus, proven feasible.